A Descriptive Qualitative Study of Ninth-Grade Students’ Ability in Writing Recount Texts at SMP Negeri 3 Metro - Amalia Husna Nailuzzakiyah; Yeasy Agustina Sari (Prodi Tadris Bahasa Inggris, 2026)
Writing recount texts remains a challenging task for many English as a Foreign Language (EFL) learners, particularly at the junior high school level. Although numerous studies have investigated students’ writing performance, limited research has qualitatively examined students’ recount writing ability across multiple writing aspects within a natural classroom context. Therefore, this study aimed to explore the ability of ninth-grade students at SMP Negeri 3 Metro in writing recount texts. A descriptive qualitative approach was employed to analyze students’ writing based on five aspects: content, organization, grammar, vocabulary, and mechanics using Heaton’s framework. Data were collected through writing tasks, classroom observation, interviews, and documentation. The analysis focused on identifying patterns, strengths, and weaknesses in students’ writing. The findings reveal that students generally demonstrate adequate ability in organizing recount texts and conveying ideas. However, grammatical accuracy and vocabulary usage remain the main challenges affecting writing quality. This study highlights the importance of integrating vocabulary development and grammar support in EFL writing instruction. The findings provide pedagogical insights for improving writing teaching practices at the junior high school level.